Separation membranes, methods of making and using the same
Patent Information
- Application Number
- CN202210555981.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-20
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-05-20
AI Technical Summary
[0003]然而,现有的商业纳滤膜不是针对镁锂分离而设计的,其对于镁离子与锂离子的分离效率非常低,镁锂分离系数一般小于5,不能用于盐湖提锂
[0011]本发明提供的分离膜,表面的交联密度和正电荷密度较高,能够更好的截留镁离子,同时使得锂离子尽可能的通过,获得较高的镁锂分离效率,同时还具有较高的水通量,处理效率更高。并且,本发明提供的制备方法,简单,具有广阔的产业化前景。
Smart Images

Figure CN117123070B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membranes, and more specifically to a separation membrane, its preparation method, and its application. Background Technology
[0002] With the widespread application of new energy vehicles, the demand for lithium energy is gradually increasing. In my country, the vast majority of lithium resources are found in salt lake brines. Besides lithium ions, salt lake water also contains large amounts of magnesium and sodium ions, making the extraction of pure lithium resources from salt lakes technically challenging. Researchers have developed a series of methods and processes to obtain lithium resources, including precipitation, solar pond methods, extraction, calcination, membrane separation, and adsorption. Among these, membrane separation and adsorption methods have been the most extensively studied.
[0003] However, existing commercial nanofiltration membranes are not designed for magnesium-lithium separation; their separation efficiency for magnesium and lithium ions is very low, with a magnesium-lithium separation coefficient generally less than 5, making them unsuitable for lithium extraction from salt lakes. Therefore, achieving efficient magnesium-lithium separation remains a significant challenge. Summary of the Invention
[0004] The purpose of this invention is to overcome the aforementioned problems in the prior art and to provide a separation membrane, its preparation method, and its application. This separation membrane can better retain magnesium ions, achieve higher magnesium-lithium separation efficiency, and also has a higher water flux, resulting in higher treatment efficiency.
[0005] To achieve the above objectives, the present invention provides a separation membrane, which sequentially comprises a substrate layer, a porous support layer, a polyamide layer, and a modification layer;
[0006] The crosslinked polymer forming the modified layer includes structural units provided by tannic acid and structural units provided by polyamine, and at least some of the structural units provided by tannic acid are also connected to the polyamide layer through the ortho position of phenolic hydroxyl groups.
[0007] A second aspect of the present invention provides a method for preparing a separation membrane, the method comprising: sequentially preparing a porous support layer, a polyamide layer and a modification layer on a substrate layer;
[0008] The modified layer is obtained by reacting tannic acid and polyamine on the surface of a polyamide layer.
[0009] A third aspect of the present invention provides a separation membrane prepared by the method described above.
[0010] The fourth aspect of the present invention provides the application of the separation membrane as described in the first or third aspect in the separation of magnesium and lithium.
[0011] The separation membrane provided by this invention has a high cross-linking density and positive charge density on its surface, which enables better retention of magnesium ions while allowing lithium ions to pass through as much as possible, resulting in high magnesium-lithium separation efficiency. It also has a high water flux, leading to even higher treatment efficiency. Furthermore, the preparation method provided by this invention is simple and has broad industrialization prospects. Attached Figure Description
[0012] Figure 1 These are the infrared spectra of the films prepared in Example 1 and Comparative Examples 1-2 of this invention. Detailed Implementation
[0013] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0014] In a first aspect, the present invention provides a separation membrane, the separation membrane comprising, in sequence, a substrate layer, a porous support layer, a polyamide layer and a modification layer;
[0015] The crosslinked polymer forming the modified layer includes structural units provided by tannic acid and structural units provided by polyamine, and at least some of the structural units provided by tannic acid are also connected to the polyamide layer through the ortho position of phenolic hydroxyl groups.
[0016] The inventors of this invention discovered in their research that the modified layer described above has a high crosslinking density and positive charge density on its surface, which better repels divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the separation membrane, while allowing monovalent lithium ions to pass through as much as possible, thereby achieving a high magnesium-lithium separation efficiency. Furthermore, the polyamide layer contains amino groups, which also effectively retain divalent magnesium ions. Moreover, under the combined effect of the above layers, the separation membrane has a high water flux, resulting in higher processing efficiency when applied to the separation of magnesium and lithium in liquids.
[0017] According to the present invention, preferably, the thickness of the separation membrane is 100-200 μm.
[0018] According to the present invention, preferably, the thickness of the porous support layer is 10-100 μm, more preferably 30-60 μm.
[0019] According to the present invention, preferably, the thickness of the polyamide layer is 10-500 nm, more preferably 50-150 nm.
[0020] According to the present invention, preferably, the thickness of the modified layer is 1-200 nm, more preferably 10-60 nm.
[0021] The inventors of this invention discovered in their research that when the thickness range of each layer is met, the layers can work together better, enabling the separation membrane to achieve both higher magnesium-lithium separation efficiency and water flux.
[0022] According to the present invention, the material of the substrate layer is not particularly limited and can be any commonly used material in the art that has a certain strength and is suitable for nanofiltration or reverse osmosis, providing a support function. However, preferably, the material of the substrate layer is selected from at least one of polyester nonwoven fabric, polyethylene nonwoven fabric, and polypropylene nonwoven fabric.
[0023] According to the present invention, the material of the porous support layer is not particularly limited and can be any material commonly used in the art that can provide a certain supporting function and form a porous structure. More preferably, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride, and polyaryl etherketone. The porous structure in the porous support layer allows liquid to flow through it more easily. The number average molecular weight of the material of the porous support layer can be 50,000-100,000 g / mol.
[0024] According to the present invention, preferably, the polyamide layer is synthesized from a polyamine and a polyacrylamide chloride, wherein the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine and p-phenylenediamine, and more preferably at least one of polyethyleneimine, piperazine and polyethylenepolyamine.
[0025] According to the present invention, preferably, the polyacrylamide chloride is selected from at least one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and orthophthaloyl chloride, more preferably at least one of trimesoyl chloride and terephthaloyl chloride. When there are multiple polyacrylamide chlorides, their specific types can be mixed in any proportion. For example, when the polyacrylamide chloride is trimesoyl chloride and terephthaloyl chloride, the weight ratio of trimesoyl chloride to terephthaloyl chloride can be 1:1-10.
[0026] As described above, the polyamide layer has a more suitable cross-linking structure, and the amino groups therein can better retain divalent magnesium ions.
[0027] According to the present invention, preferably, the Zeta potential of the modified layer is -5mV to 30mV, more preferably 5mV to 13mV. The inventors of the present invention have also discovered that when the above potential is met, the positive charge density on the membrane surface is higher, which allows for better retention of magnesium ions and better passage of lithium ions, thereby achieving higher magnesium-lithium separation efficiency. It is understood that the separation membrane can be measured using a Zeta potential analyzer, and the obtained potential value is the potential of the surface modified layer.
[0028] According to the present invention, preferably, the modified layer is obtained by multiple self-assembly reactions of tannic acid and polyamine on a polyamide layer; wherein the multiple self-assembly method includes: contacting one side of the polyamide layer of the material comprising a substrate layer, a porous support layer, and a polyamide layer with a tannic acid solution while maintaining a flow at 0.4-0.7 MPa, 10-30°C, and a tannic acid solution; then contacting one side of the polyamide layer of the material with a polyamine solution while maintaining a flow at 0.4-0.7 MPa, 10-30°C, and a polyamine solution, thereby completing one self-assembly reaction; repeating the above steps to complete multiple self-assembly reactions.
[0029] According to the present invention, preferably, the polyamine of the modified layer is selected from at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine, and may be the same as or different from the polyamine used to prepare the polyamide layer.
[0030] The inventors of this invention further discovered in their research that by employing the above-described method of multiple self-assemblies on the polyamide layer, a higher Zeta potential can be ensured on the modified layer, thereby further ensuring a higher magnesium-lithium separation efficiency. Compared to simply contacting the material with a tannic acid solution (or a polyamine solution), the reaction is more complete under conditions of 0.4-0.7 MPa, 10-30°C, and with the solution kept flowing.
[0031] According to the present invention, preferably, in a single self-assembly reaction, the contact time between the material and the tannic acid solution is 1-120 min, more preferably 10-60 min.
[0032] According to the present invention, preferably, in a single self-assembly reaction, the contact time between the material and the polyamine solution is 1-120 min, more preferably 10-60 min.
[0033] This ensures that both react more fully.
[0034] According to the present invention, preferably, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of polyamine in the polyamine solution is 0.1-10:1, more preferably 0.5-6:1. The above ratio promotes a more complete reaction.
[0035] According to the present invention, preferably, the concentration of tannic acid in the tannic acid solution and the concentration of polyamine in the polyamine solution are each independently 0.00001-1 wt%, more preferably 0.0001-0.1 wt%.
[0036] According to the present invention, preferably, the number of self-assembly reactions is 1-10 times, more preferably 2-5 times. This further ensures that the obtained modified layer has a high Zeta potential.
[0037] When the conditions for various self-assembly reactions mentioned above are met, it can be further ensured that the obtained modified layer has a high Zeta potential, and further ensure that a high magnesium-lithium separation efficiency is obtained.
[0038] According to a preferred embodiment of the present invention, the water flux of the separation membrane is greater than or equal to 20 L·m -2 ·h -1 The MgCl2 desalination rate is greater than or equal to 99%; the magnesium-lithium separation coefficient is greater than or equal to 70.
[0039] In a second aspect, the present invention provides a method for preparing a separation membrane, characterized in that the method includes: sequentially preparing a porous support layer, a polyamide layer and a modification layer on a substrate layer;
[0040] The modified layer is obtained by reacting tannic acid and polyamine on the surface of a polyamide layer.
[0041] It is understandable that tannic acid and polyamines can undergo a Michael addition reaction to form a cross-linked structure. The carbon atom adjacent to the carbon atom containing the phenolic hydroxyl group on the tannic acid acts as a reaction site and reacts with the polyamine. When reacting on the surface of the polyamide layer, the carbon atom adjacent to the carbon atom containing the phenolic hydroxyl group on the tannic acid acts as a reaction site and reacts with the amino group in the polyamide layer.
[0042] The method for preparing the porous support layer on the substrate layer can be a commonly used method in the art. However, preferably, the method for preparing the porous support layer includes: coating a porous support layer material solution onto the substrate layer and immersing it in water at 10-30°C for 10-60 minutes.
[0043] The specific method of coating is not particularly restricted; a scraper can be used for coating.
[0044] According to the present invention, preferably, the thickness of the substrate layer is 30-150 μm, more preferably 50-120 μm. It is understood that the thickness of the substrate layer remains substantially unchanged before and after preparation.
[0045] The available materials for the substrate layer have already been described and will not be repeated here.
[0046] Preferably, the conditions for preparing the porous support layer include a thickness of 10-100 μm in the separation membrane, more preferably 30-60 μm. It is understood that the thickness can be controlled by controlling the amount of coating applied, and since thickness collapse occurs after coating, the thickness set during coating will differ somewhat from the final thickness of the porous support layer in the prepared separation membrane. Generally, the thickness set during coating is approximately 40-60 μm greater than the desired porous support layer thickness in the separation membrane.
[0047] According to the present invention, preferably, the concentration of the porous support layer material in the porous support layer material solution is 10-20 wt%. The specific types of porous support layer materials that can be selected have already been described and will not be repeated here.
[0048] According to the present invention, preferably, the solvent for the porous support layer material solution is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide. For example, in the preparation, the porous support layer material is first dissolved in the solvent and degassed (degassed at 20-40°C for 10-180 min) to obtain the porous support layer material solution.
[0049] When the porous support layer is prepared using the method described above, the solvent of the porous support layer material solution gradually leaves the porous support layer when it is immersed in water. Through this phase transformation method, it is possible to further ensure that a support layer with a porous structure is obtained.
[0050] After the porous support layer is prepared, the material can be washed, such as by multiple water washes.
[0051] According to the present invention, a preferred method for preparing the polyamide layer includes: sequentially contacting the surface of a porous support layer, comprising a substrate layer and a porous support layer, with an aqueous phase containing a polyamine and an organic phase containing a polyacrylamide chloride, followed by heat treatment. By employing the above-described method of sequentially contacting the aqueous phase containing a polyamine and the organic phase containing a polyacrylamide chloride, a polyamide layer is obtained through interfacial polymerization. This polyamide layer has a cross-linked structure and is not only dense but also very thin, further ensuring high magnesium-lithium separation efficiency and water flux. The contacting of the aqueous and organic phases can be performed at room temperature, such as 23-28°C.
[0052] According to the present invention, preferably, the conditions for preparing the polyamide layer include making the thickness of the polyamide layer in the separation membrane 10-500 nm, more preferably 50-300 nm.
[0053] According to the present invention, preferably, the contact time between the porous support layer and the aqueous phase containing polyamine is 5-100s, more preferably 10-60s.
[0054] According to the present invention, preferably, the contact time between the porous support layer and the organic phase containing polyacrylamide chloride is 10-200 s, more preferably 20-120 s.
[0055] According to the present invention, preferably, the ratio of the concentration of the polyamine in the aqueous phase containing the polyamine to the concentration of the polyacrylamide in the organic phase containing the polyacrylamide is (0.1-10):1, more preferably (0.5-8):1. The inventors of the present invention have also found that satisfying the above ratio further ensures higher magnesium-lithium separation efficiency and water flux.
[0056] The organic solvent in the organic phase containing polyacrylamide chloride can be one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (which can be commercially available Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).
[0057] According to the present invention, preferably, the concentration of the polyamine in the aqueous phase containing the polyamine is 0.1-10 wt%, more preferably 0.5-2.5 wt%.
[0058] According to the present invention, preferably, the concentration of the polyacryl chloride in the organic phase containing the polyacryl chloride is 0.01-1 wt%, more preferably 0.1-0.5 wt%. When there are multiple polyacryl chlorides, their specific types can be mixed in any proportion. For example, when the polyacryl chlorides are trimesoyl chloride and terephthaloyl chloride, the weight ratio of trimesoyl chloride to terephthaloyl chloride can be 1:1-10.
[0059] The volume of the aqueous phase containing polyamines and the volume of the organic phase containing polyacrylamide chlorides are not particularly limited, as long as the amount of polyamines in the aqueous phase or the amount of polyacrylamide chlorides in the organic phase can be guaranteed to form a suitable polyamide layer with a cross-linked structure on the membrane. Preferably, relative to 400 cm⁻¹, 2 The membrane area, the total amount of polyamines in the aqueous phase can be 0.05-2g, and the total amount of polyacrylamide chlorides in the organic phase can be 0.0001-0.5g.
[0060] Under the conditions of the above concentration and contact time, the thickness of the polyamide layer can generally be 10-500 nm.
[0061] Within the above concentration range, it can also achieve a higher rejection rate for magnesium ions while having a higher permeability for monovalent lithium ions.
[0062] The specific types of polyamines and polyacryl chlorides have already been explained and will not be repeated here.
[0063] According to the present invention, preferably, the heat treatment temperature is 40-150°C, more preferably 50-120°C; the heat treatment time is 0.5-10 min, more preferably 1-5 min. It is understood that polyamines and polyacrylamide chlorides will react upon contact, but meeting the above heat treatment conditions ensures a more complete reaction and a denser polyamide separation layer.
[0064] According to the present invention, preferably, the method for preparing the modified layer includes: obtaining it by subjecting tannic acid and polyamine to a polyamide layer through multiple self-assembly reactions; wherein the multiple self-assembly method includes: contacting one side of the polyamide layer of the material comprising a substrate layer, a porous support layer, and a polyamide layer with a tannic acid solution while maintaining a flow at 0.4-0.7 MPa, 10-30°C, and a polyamine solution; then contacting one side of the polyamide layer of the material with a polyamine solution while maintaining a flow at 0.4-0.7 MPa, 10-30°C, and a polyamine solution, completing one self-assembly reaction; repeating the above steps to complete multiple self-assembly reactions. The self-assembly reaction can be carried out in a cross-flow membrane tank, where water is circulated into the membrane tank by a water pump to keep the water in the membrane tank in a flowing state and under a certain pressure, which can be controlled by a pressure regulating valve. Cross-flow membrane tanks are commonly used equipment, and the method of the present invention can be carried out in common equipment, with a simple process and easy industrialization. In the process of self-assembly reaction in the cross-flow membrane tank, for example, after tannic acid comes into contact with the material, the tannic acid solution is discharged and the cross-flow membrane tank is repeatedly rinsed with deionized water to clean the tannic acid in the system, which will also wash the surface of the material.
[0065] In the cross-flow membrane tank, the pump continuously delivers solution to the tank. Therefore, the total amount of tannic acid or polyamine in the solution generally exceeds the amount that can adhere to the membrane surface for reaction, ensuring the acquisition of a modified layer with a suitable structure. The solution flow rate can be 0.5-5 L / min.
[0066] According to the present invention, preferably, in a single self-assembly reaction, the contact time between the material and the tannic acid solution is 1-120 min, more preferably 10-60 min.
[0067] According to the present invention, preferably, in a single self-assembly reaction, the contact time between the material and the polyamine solution is 1-120 min, more preferably 10-60 min.
[0068] Preferably, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of polyamine in the polyamine solution is 1:0.5-6. Meeting this ratio further ensures that the self-assembly reaction proceeds more fully.
[0069] More preferably, the concentration of tannic acid in the tannic acid solution and the concentration of polyamine in the polyamine solution are each independently 0.00001-1 wt%, and even more preferably 0.001-0.1 wt%.
[0070] Preferably, the number of self-assembly reactions is 1-10 times, more preferably 2-5 times.
[0071] Within the above concentration and time range, a modified layer with a thickness of 1-200 nm can generally be obtained.
[0072] According to the present invention, preferably, the polyamine used to prepare the modified layer is selected from at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine.
[0073] The inventors of this invention discovered during their research that when the modified layer is prepared using the method described above, the surface crosslinking density and positive charge density of the prepared membrane are higher, resulting in higher magnesium-lithium separation efficiency. After preparation, the separation membrane can be immersed in deionized water for later use.
[0074] Thirdly, the present invention provides a separation membrane prepared by the method described above.
[0075] Fourthly, the present invention provides the application of the separation membrane as described in the first or third aspect in magnesium-lithium separation (especially lithium extraction from salt lakes).
[0076] According to a particularly preferred embodiment of the present invention, a separation membrane is prepared according to the following method:
[0077] A polysulfone solution with a polysulfone concentration of 16-19% by weight is coated onto a polyester nonwoven fabric (substrate layer) with a thickness of 75-80μm using a doctor blade. The material is then immersed in water at a temperature of 24-26℃ for 45-60 minutes, which allows the polysulfone layer on the surface of the polyester nonwoven fabric to undergo phase transformation into a porous membrane. Finally, after 2-3 water washings, a material including a substrate layer and a porous support layer (the thickness of the porous support layer is about 38-42μm) is obtained.
[0078] The porous support layer, comprising a substrate layer and a porous support layer, is contacted with an aqueous solution containing 0.5-0.6% by weight of polyethyleneimine at 24-26°C for 50-60 seconds, after which the solution is drained. Then, the upper surface of the support layer is contacted again with an Isopar E solution containing trimesoyl chloride and terephthaloyl chloride (the ratio of the concentration of polyamine in the aqueous phase containing polyamine to the concentration of polyacrylamide in the organic phase containing polyacrylamide is 5-6:1, and the ratio of the concentration of trimesoyl chloride to terephthaloyl chloride is 1:3-5), at 24-26°C for 60-70 seconds, after which the solution is drained. Finally, the membrane is placed in an oven and heated at 60-70°C for 3-4 minutes.
[0079] The heat-treated product is loaded into a cross-flow membrane tank, with the polyamide layer of the material in contact with the solution in the tank. The solution in the cross-flow membrane tank is a 0.001-0.005 wt% aqueous solution of tannic acid. The cross-flow membrane tank is operated for 30-35 minutes at 0.6-0.65 MPa, 25-26℃, and a solution flow rate of 2.5-3.5 L / min. Afterward, the solution is drained, and the cross-flow membrane tank is repeatedly rinsed with deionized water to remove the tannic acid from the system. Polyamide is then added to the cross-flow membrane tank. An aqueous solution of polyimide (the ratio of tannic acid concentration in the tannic acid solution to the polyamine concentration in the polyamine solution is 1:3-4) is used to contact the polyamide layer of the material with the above solution. After the cross-flow membrane tank is run at 0.6-0.65 MPa and 25-26℃ for 30-35 minutes, the liquid is drained and the cross-flow membrane tank is repeatedly rinsed with deionized water to wash away the residual polyethyleneimine. This completes one self-assembly reaction. The above operation is repeated to complete another self-assembly reaction to obtain the separation membrane.
[0080] The present invention will be described in detail below through embodiments, wherein,
[0081] IsoparE is a commercially available alkane solvent oil (purchased from Xilong Chemical).
[0082] In the following embodiments, when the material including the substrate layer, the porous support layer, and the polyamide layer comes into contact with the solution in the cross-flow membrane tank, water is pumped into the membrane tank by a water pump to keep the water in the membrane tank in a flowing state and with a certain pressure, and the flow rate is 3L / min.
[0083] Except for Examples 9-10, in the other examples and comparative examples, the materials including the substrate layer and the porous support layer were prepared according to the following method:
[0084] Polysulfone (number-average molecular weight 80,000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18% by weight. The solution was then degassed at 25°C for 120 min. Next, the polysulfone solution was coated onto a 75 μm thick polyester nonwoven fabric (substrate layer) using a doctor blade. The material was then immersed in water at 25°C for 60 min, causing the polysulfone layer on the surface of the polyester nonwoven fabric to undergo phase inversion into a porous membrane. Finally, after three water washes, a material with a total thickness of 115 μm, including the substrate layer and a porous support layer (40 μm thick), and an area of 400 cm² was obtained. 2 .
[0085] The membranes prepared in the following examples and comparative examples were immersed in deionized water for 24 hours after preparation for later use, and then various properties and parameters were measured.
[0086] Example 1
[0087] The porous support layer, comprising a substrate layer and a porous support layer, was contacted with an aqueous solution (50 ml) containing 0.5 wt% polyethyleneimine at 25°C for 60 s, and then drained. Next, the upper surface of the support layer was contacted with an Isopar E solution (30 ml) containing 0.02 wt% trimesoyl chloride and 0.08 wt% terephthaloyl chloride at 25°C for 60 s, and then drained. Finally, the membrane was placed in an oven and heated at 70°C for 3 min.
[0088] The heat-treated product was loaded into a cross-flow membrane tank, with the polyamide layer of the material in contact with the solution in the tank. The solution in the cross-flow membrane tank was a 0.001 wt% aqueous solution of tannic acid. After the cross-flow membrane tank was run at 0.6 MPa and 25°C for 30 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove the tannic acid from the system. A 0.004 wt% aqueous solution of polyethyleneimine was added to the cross-flow membrane tank, with the polyamide layer of the material in contact with the solution. After the cross-flow membrane tank was run at 0.6 MPa and 25°C for 30 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove the residual polyethyleneimine. This completed one self-assembly reaction. The above operation was repeated to complete another self-assembly reaction, resulting in a separation membrane.
[0089] Example 2
[0090] The porous support layer, comprising a substrate layer and a porous support layer, was contacted with an aqueous solution (50 ml) containing 1.0 wt% polyethylenepolyamine at 25°C for 20 s, and then drained. Next, the upper surface of the support layer was contacted with an Isopar E solution (30 ml) containing 0.18 wt% trimesoyl chloride and 0.12 wt% terephthaloyl chloride at 25°C for 30 s, and then drained. Finally, the membrane was placed in an oven and heated at 50°C for 5 min.
[0091] The heat-treated product was loaded into a cross-flow membrane tank, with the polyamide layer of the material in contact with the solution in the tank. The solution in the cross-flow membrane tank was a 0.01 wt% aqueous solution of tannic acid. After the cross-flow membrane tank was run at 0.4 MPa and 15 °C for 40 min, the solution was drained, and the solution in the cross-flow membrane tank was repeatedly rinsed with deionized water to remove residual tannic acid. A 0.045 wt% aqueous solution of polyethyleneimine was added to the cross-flow membrane tank, with the polyamide layer of the material in contact with the solution. After the cross-flow membrane tank was run at 0.4 MPa and 15 °C for 40 min, the solution was drained, and the cross-flow membrane tank was repeatedly rinsed with deionized water to remove residual polyethyleneimine. This completed one self-assembly reaction. The above operation was repeated to complete another self-assembly reaction, resulting in a separation membrane.
[0092] Example 3
[0093] The porous support layer, comprising a substrate layer and a porous support layer, was contacted with an aqueous solution (50 ml) containing 2.5 wt% piperazine at 25°C for 40 s, and then drained. The upper surface of the support layer was then contacted with an Isopar E solution (30 ml) containing 0.2 wt% trimesoyl chloride and 0.1 wt% terephthaloyl chloride at 25°C for 100 s, and then drained. The membrane was then placed in an oven and heated at 110°C for 1 min.
[0094] The heat-treated product was loaded into a cross-flow membrane tank, with the polyamide layer of the material in contact with the solution in the tank. The solution in the cross-flow membrane tank was a 0.1 wt% aqueous solution of tannic acid. After the cross-flow membrane tank was run at 0.7 MPa and 30°C for 20 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove residual tannic acid. A 0.1 wt% aqueous solution of polyethyleneimine was then added to the cross-flow membrane tank, with the polyamide layer of the material in contact with the solution. After the cross-flow membrane tank was run at 0.7 MPa and 30°C for 20 min, the solution was drained, and the tank was repeatedly rinsed with deionized water to remove residual polyethyleneimine. This completed one self-assembly reaction. The above operation was repeated to complete another self-assembly reaction, resulting in a separation membrane.
[0095] Example 4
[0096] The separation membrane was prepared according to the method of Example 1, except that polyethyleneimine was replaced with polyethylenepolyamine in the self-assembly reaction.
[0097] Example 5
[0098] The separation membrane was prepared according to the method of Example 1, except that in the self-assembly reaction, polyethyleneimine was replaced with tetraethylenepentamine.
[0099] Example 6
[0100] The separation membrane was prepared according to the method of Example 1, except that in the self-assembly reaction, polyethyleneimine was replaced with triethylenetetramine.
[0101] Example 7
[0102] The separation membrane was prepared according to the method of Example 1, except that the self-assembly reaction was carried out only once.
[0103] Example 8
[0104] The separation membrane was prepared according to the method in Example 1, except that the self-assembly reaction was carried out five times.
[0105] Example 9
[0106] The separation membrane was prepared according to the method of Example 1, except that the material comprising the substrate layer and the porous support layer was prepared as follows: Polyethersulfone (number average molecular weight of 70,000 g / mol) was dissolved in N,N-dimethylformamide to obtain a polyethersulfone solution with a concentration of 20% by weight, and degassed at 25°C for 120 min. Then, the polyethersulfone solution was coated onto a 100 μm thick polyethylene nonwoven fabric (substrate layer) using a doctor blade, and the material was then immersed in water at 23°C for 20 min, so that the polyethersulfone layer on the surface of the polyethylene nonwoven fabric underwent phase inversion to form a porous membrane. Finally, after three water washes, a material with a total thickness of 135 μm, comprising the substrate layer and the porous support layer (the porous support layer is 35 μm thick), and an area of 400 cm² was obtained. 2 .
[0107] Example 10
[0108] The separation membrane was prepared according to the method of Example 1, except that the material comprising the substrate layer and the porous support layer was prepared as follows: Polyacrylonitrile (number average molecular weight of 100,000 g / mol) was dissolved in N,N-dimethylformamide to obtain a polyacrylonitrile solution with a concentration of 15% by weight, and degassed at 25°C for 120 min. Then, the polyacrylonitrile solution was coated onto a 115 μm thick polypropylene nonwoven fabric (substrate layer) using a doctor blade, and the material was then immersed in water at 28°C for 40 min, so that the polyacrylonitrile layer on the surface of the polypropylene nonwoven fabric underwent phase inversion to form a porous membrane. Finally, after three water washes, a material with a total thickness of 160 μm, comprising the substrate layer and the porous support layer (the porous support layer is 45 μm thick), and an area of 400 cm² was obtained. 2 .
[0109] Example 11
[0110] The separation membrane was prepared according to the method in Example 1, except that the heat-treated product was not placed in a cross-flow membrane tank for self-assembly. Instead, the polyamide layer of the material was directly placed in a beaker containing an aqueous solution of tannic acid (i.e., the pressure could not be controlled and the solution was not flowing) for 30 minutes, then removed and repeatedly rinsed with deionized water. Then, the polyamide layer of the material was directly placed in a beaker containing an aqueous solution of polyethyleneimine for 30 minutes, then removed and repeatedly rinsed with deionized water. This process was repeated to complete another self-assembly reaction, resulting in the separation membrane. In each self-assembly, the volume of the tannic acid solution (or polyamine) in the beaker was such that the total amount of tannic acid (or polyamine) exceeded the amount that could potentially adhere to the membrane and react.
[0111] Example 12
[0112] The separation membrane was prepared according to the method of Example 1, except that the concentration of tannic acid in the tannic acid aqueous solution was 0.0001 wt%, and the concentration of polyamine in the polyamine solution was 0.5 wt%.
[0113] Comparative Example 1
[0114] The separation membrane was prepared according to the method of Example 1, except that no self-assembly reaction was performed, that is, the separation membrane was obtained directly after heat treatment.
[0115] Comparative Example 2
[0116] The separation membrane was prepared according to the method of Example 1, except that the heat-treated product was placed in a cross-flow membrane cell containing 0.001 wt% tannic acid aqueous solution, and after running at 0.6 MPa and 25°C for 30 min, it was taken out to obtain the separation membrane (i.e., it was only in contact with the tannic acid aqueous solution once).
[0117] Comparative Example 3
[0118] The separation membrane was prepared according to the method of Example 1, except that polyethyleneimine was replaced with polyvinyl alcohol.
[0119] Test Example 1
[0120] The separation membranes prepared in Example 1 and Comparative Examples 1-2 were characterized by infrared spectroscopy, and the results are shown in the figure. Figure 1 .
[0121] As can be seen, the membrane without the self-assembly modification of tannic acid and polyethyleneimine (the membrane of Comparative Example 1) has a lower viscosity at 3388 cm⁻¹. -1 It exhibits a broad peak at 1507 cm⁻¹, corresponding to the unreacted amino groups on the polyamide surface, and also shows a peak at 1507 cm⁻¹. -1 A weak signal was observed at this location, corresponding to the stretching vibration of NH. After modification with tannic acid (i.e., the membrane of Comparative Example 2), the membrane measured at 3364 cm⁻¹... -1 There is a strong absorption peak at 1507 cm⁻¹, corresponding to the phenolic hydroxyl group in the tannic acid molecule. -1 The signal peak at 3270-3390 cm⁻¹ essentially disappeared, confirming that a chemical reaction occurred between the amino group and tannic acid. After two consecutive self-assemblies of tannic acid and polyethyleneimine on the polyamide surface (the film of Example 1), the signal peak at 3270-3390 cm⁻¹... -1 A broad peak appears at 1507 cm⁻¹, corresponding to unreacted amino and unreacted phenolic hydroxyl groups on the modified layer; simultaneously, a peak appears at 1507 cm⁻¹. -1 The enhanced signal at the location confirmed that polyethyleneimine was modified onto the surface of the membrane. Combined with the operation and infrared image of Comparative Example 2, it can be seen that for the membrane of Example 1, the crosslinked polymer forming the modified layer comprises structural units provided by tannic acid and structural units provided by polyamine, the structural units provided by tannic acid also being connected to the polyamide layer via ortho-positions of phenolic hydroxyl groups.
[0122] The infrared characterization results of the membranes in Examples 2-11 are similar to those in Example 1 (not shown in the figures).
[0123] Test Example 2
[0124] The separation membranes prepared in the above examples and comparative examples were subjected to the following measurements:
[0125] The thicknesses of the membrane, porous support layer, and polyamide layer were measured using a micrometer and a scanning electron microscope. The thickness of the modification layer was obtained by subtracting the thicknesses of the substrate layer, porous support layer, and polyamide layer from the membrane thickness. The thickness of the substrate layer was the same as the thickness measured before coating the porous support layer material solution.
[0126] The zeta potential of each membrane surface was measured using a zeta potential analyzer.
[0127] Each membrane was separately placed in a cross-flow membrane tank. The water permeation rate of the separation membrane was measured over 1 hour at 0.6 MPa and 25°C. The water flux was then calculated using the following formula:
[0128] J = Q / (A·t), where J is the water flux, Q is the water permeation rate (L), and A is the effective membrane area of the composite nanofiltration membrane (m²). 2 ), where t is time (h).
[0129] The separation membrane was loaded into a cross-flow membrane tank containing a feed solution with 2000 ppm magnesium chloride and 100 ppm lithium chloride. After pre-compression at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.6 MPa. The concentrations of magnesium chloride and lithium chloride in the permeate were measured by ion chromatography, and the desalination rate was calculated using the following formula:
[0130] R = (C p -C f ) / C p ×100%, where R is the desalination rate, and C is the desalination rate. p C represents the concentration of magnesium chloride or lithium chloride in the feed solution (measured by ion chromatography). f The concentration of magnesium chloride or lithium chloride in the permeate (measured by ion chromatography);
[0131] The lithium-magnesium separation coefficient is calculated using the following formula:
[0132]
[0133] Where S is the lithium-magnesium separation coefficient, and C Li,p and C Li,f The concentrations of lithium ions in the permeate and feed solution, respectively (measured by ion chromatography); C Mg,p and C Mg,fThe concentrations of magnesium ions in the permeate and feed solution are respectively (measured by ion chromatography).
[0134] The results are shown in Table 1-2.
[0135] Table 1
[0136]
[0137] Table 2
[0138]
[0139]
[0140] In Comparative Example 2, the thickness of the modified layer was due to the change in thickness caused by tannic acid; in Comparative Example 3, the thickness of the modified layer was due to the change in thickness caused by the reaction of tannic acid and polyvinyl alcohol.
[0141] As can be seen from Tables 1-2, the embodiments using the technical solution of the present invention have both higher water flux and higher magnesium-lithium separation efficiency.
[0142] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A separation membrane, characterized in that, The separation membrane comprises, in sequence, a substrate layer, a porous support layer, a polyamide layer, and a modification layer; The crosslinked polymer forming the modified layer includes structural units provided by tannic acid and structural units provided by polyamine, and at least some of the structural units provided by tannic acid are also connected to the polyamide layer through the ortho position of phenolic hydroxyl groups; The Zeta potential of the modified layer is 5mV to 13mV; The modified layer is obtained by multiple self-assembly reactions of tannic acid and polyamine on a polyamide layer. The multiple self-assembly method includes: contacting one side of the polyamide layer of a material comprising a substrate layer, a porous support layer, and a polyamide layer with a tannic acid solution at 0.4-0.7 MPa, 10-30°C, and while the tannic acid solution remains flowing; then, contacting the polyamide layer of the material with a polyamine solution at 0.4-0.7 MPa, 10-30°C, and while the polyamine solution remains flowing, completing one self-assembly reaction; repeating the above steps to complete multiple self-assembly reactions. The polyamine used to prepare the modified layer is selected from at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine.
2. The separation membrane according to claim 1, wherein, The thickness of the separation membrane is 100-200 μm; And / or, the thickness of the substrate layer is 30-150 μm; And / or, the thickness of the porous support layer is 10-100 μm; And / or, the thickness of the polyamide layer is 10-500 nm; And / or, the thickness of the modification layer is 1-200 nm.
3. The separation membrane according to claim 1, wherein, The thickness of the substrate layer is 50-120 μm; And / or, the thickness of the porous support layer is 30-60 μm; And / or, the thickness of the polyamide layer is 50-150 nm; And / or, the thickness of the modification layer is 10-60 nm.
4. The separation membrane according to claim 1 or 2, wherein, The material of the substrate layer is selected from at least one of polyester nonwoven fabric, polyethylene nonwoven fabric and polypropylene nonwoven fabric; And / or, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryl etherketone.
5. The separation membrane according to claim 1 or 2, wherein, The polyamide layer is synthesized from a polyamine and a polyacrylamide chloride, wherein the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine, and p-phenylenediamine.
6. The separation membrane according to claim 5, wherein, The polyacryl chloride is selected from at least one of pyromellitic chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride.
7. The separation membrane according to claim 6, wherein, The polyacryl chloride is selected from at least one of pyromellitic methyl chloride and terephthaloyl chloride.
8. The separation membrane according to claim 1, wherein, In a single self-assembly reaction, the contact time between the material and the tannic acid solution is 1-120 min; And / or, in a single self-assembly reaction, the contact time between the material and the polyamine solution is 1-120 min; And / or, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of polyamine in the polyamine solution is 0.1-10:1; And / or, the concentration of tannic acid in the tannic acid solution and the concentration of polyamine in the polyamine solution are each independently 0.00001-1 wt%.
9. The separation membrane according to claim 1, wherein, In a single self-assembly reaction, the contact time between the material and the tannic acid solution is 10-60 min; And / or, in a single self-assembly reaction, the contact time between the material and the polyamine solution is 10-60 min; And / or, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of polyamine in the polyamine solution is 0.5-6:1; And / or, the concentration of tannic acid in the tannic acid solution and the concentration of polyamine in the polyamine solution are each independently 0.0001-0.1 wt%; And / or, the number of self-assembly reactions is 2-5 times.
10. A method for preparing the separation membrane according to claim 1, characterized in that, The method includes: sequentially preparing a porous support layer, a polyamide layer, and a modification layer on a substrate layer; The modified layer is obtained by reacting tannic acid and polyamine on the surface of a polyamide layer; The method for preparing the modified layer includes: reacting tannic acid and polyamine on a polyamide layer through multiple self-assembly reactions; wherein the multiple self-assembly method includes: contacting one side of the polyamide layer of a material comprising a substrate layer, a porous support layer, and a polyamide layer with a tannic acid solution while maintaining a flow at 0.4-0.7 MPa, 10-30°C, and a flowing polyamine solution; then contacting one side of the polyamide layer of the material with a polyamine solution while maintaining a flow at 0.4-0.7 MPa, 10-30°C, and a flowing polyamine solution to complete one self-assembly reaction; repeating the above steps to complete multiple self-assembly reactions; The polyamine used to prepare the modified layer is selected from at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine, and polyethylenepolyamine.
11. The method according to claim 10, wherein, The method for preparing a porous support layer includes: coating a porous support layer material solution onto a substrate layer and immersing it in water at 10-30°C for 10-60 minutes.
12. The method according to claim 11, wherein, The thickness of the substrate layer is 30-150μm; And / or, the material of the substrate layer is selected from at least one of polyester nonwoven fabric, polyethylene nonwoven fabric and polypropylene nonwoven fabric; And / or, the conditions for preparing the porous support layer include making the thickness of the porous support layer in the separation membrane 10-100 μm; And / or, the concentration of the porous support layer material in the porous support layer material solution is 10-20 wt%; And / or, the material of the porous support layer is selected from at least one of polyethersulfone, polysulfone, polyaryl ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryl etherketone; And / or, the solvent of the porous support layer material solution is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
13. The method according to claim 12, wherein, The thickness of the substrate layer is 50-120μm; And / or, the conditions for preparing the porous support layer include making the thickness of the porous support layer in the separation membrane 30-60 μm.
14. The method of claim 10, wherein, The method for preparing the polyamide layer includes: sequentially contacting the surface of a porous support layer, which comprises a substrate layer and a porous support layer, with an aqueous phase containing polyamines and an organic phase containing polyacrylamide chlorides, followed by heat treatment.
15. The method according to claim 14, wherein, The conditions for preparing the polyamide layer include making the thickness of the polyamide layer in the separation membrane 10-500 nm; And / or, the porous support layer is in contact with the aqueous phase containing polyamines for 5-100 s; And / or, the contact time between the porous support layer and the organic phase containing polyacrylamide chloride is 10-200 s; And / or, the ratio of the concentration of polyamine in the aqueous phase containing polyamine to the concentration of polyacryl chloride in the organic phase containing polyacryl chloride is (0.1-10):1; And / or, the concentration of polyamines in the aqueous phase containing polyamines is 0.1-10 wt%; And / or, the concentration of polyacryl chlorides in the organic phase containing polyacryl chlorides is 0.01-1 wt%; And / or, the polyamide layer is synthesized from a polyamine and a polyacrylamide chloride, wherein the polyamine is selected from at least one of polyethyleneimine, triethylenetetramine, tetraethylenepentamine, diethylenetriamine, piperazine, m-phenylenediamine and p-phenylenediamine; And / or, the polyacryl chloride is selected from at least one of pyromellitic chloroformyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride; And / or, the heat treatment temperature is 40-150℃; the heat treatment time is 0.5-10min.
16. The method of claim 14, wherein, The conditions for preparing the polyamide layer include ensuring that the thickness of the polyamide layer in the separation membrane is 50-300 nm. And / or, the porous support layer is in contact with the aqueous phase containing polyamines for 10-60 s; And / or, the contact time between the porous support layer and the organic phase containing polyacrylamide chloride is 20-120 s; And / or, the ratio of the concentration of polyamines in the aqueous phase containing polyamines to the concentration of polyacrylamide chlorides in the organic phase containing polyacrylamide chlorides is (0.5-8):1; And / or, the concentration of polyamines in the aqueous phase containing polyamines is 0.5-2.5 wt%; And / or, the concentration of polyacryl chlorides in the organic phase containing polyacryl chlorides is 0.1-0.5 wt%; And / or, the polyacryl chloride is selected from at least one of pyromellitic methyl chloride and terephthaloyl chloride; And / or, the heat treatment temperature is 50-120℃; the heat treatment time is 1-5 min.
17. The method according to claim 10, wherein, In a single self-assembly reaction, the contact time between the material and the tannic acid solution is 1-120 min; And / or, in a single self-assembly reaction, the contact time between the material and the polyamine solution is 1-120 min; And / or, the ratio of the concentration of tannic acid in the tannic acid solution to the concentration of polyamine in the polyamine solution is 1:0.5-6; And / or, the concentration of tannic acid in the tannic acid solution and the concentration of polyamine in the polyamine solution are each independently 0.00001-1 wt.
18. The method according to claim 10, wherein, In a single self-assembly reaction, the contact time between the material and the tannic acid solution is 10-60 min; And / or, in a single self-assembly reaction, the contact time between the material and the polyamine solution is 10-60 min; And / or, the concentration of tannic acid in the tannic acid solution and the concentration of polyamine in the polyamine solution are each independently 0.001-0.1 wt%; And / or, the number of self-assembly reactions is 2-5 times.
19. The separation membrane prepared by the method according to any one of claims 10-18.
20. The application of the separation membrane according to any one of claims 1-9 and claim 19 in magnesium-lithium separation.
Citation Information
Patent Citations
Phenol-amine alternately-assembled composite nano-filtration film and preparation method thereof
CN107875868A
Nano-filtration membrane, preparation method and applications of thereof
CN109692584A